A closed-loop error compensation method for robotic flank milling. (June 2020) - Xiong, Gang; Li, Zhou-Long; Ding, Ye; Zhu, LiMin
Highlights: A closed-loop error compensation method for robotic flank milling is presented. Coordinate system alignment and surface fitting are formulated uniformly based on point-to-surface function. Machining errors are decomposed according to spatial statistical analysis technique. Compensation tool path is generated by global fitting the tool envelope surface. Abstract: Errors of diverse sources prevented industrial robots from being adopted into milling applications. This paper proposes a closed-loop error compensation method for robotic flank milling of complex shaped surfaces. First, the finished surface is measured in situ by a laser tracker based measuring system without unclamping the fixture. Then, the sampled points are mapped into the model reference coordinate system and a deterministic bicubic B-spline surface is fitted to extract the systematic components of the machining errors. Finally, the compensation tool path is directly generated for the mirror symmetry points of the only-systematic-error-contained sample points. The robot motion program is converted accordingly for further machining. The experiment shows that the surface accuracy is improved significantly in terms of the profile error via the proposed error compensation process, which well validates the effectiveness of the method.